Graphene Oxide Nanoadsorbent for the Removal of Fluoride Ion from Groundwater: Adsorbent Performance and Adsorption Mechanism. (27th April 2022) - Chufa, Bayisa Meka; Gonfa, Bedasa Abdisa; Anshebo, Teketel Yohannes
Abstract : The deterioration of the quality of groundwater by fluoride is the cause of shortage of drinking water supply in the rift valley region. Most people living in the rural areas are using groundwater as the source of their potable water; however, it is contaminated with high concentrations of fluoride ion above the permissible level. Hence, this study was designed to investigate the adsorption of fluoride from groundwater by graphene oxide (GO) under specific conditions, such as: agitation rate of 120 rpm, contact time of 90 minutes, adsorbent dosage of 0.42 mg/L, initial fluoride concentration of 10 mg/L, and pH of 6.8. The result obtained showed 99.3% fluoride removal from the NaF prepared solution and 91.6% fluoride removal from the real sample. The retained properties of GO after adsorption observed on UV–Vis analysis confirmed that the adsorbent can be recyclable. The result obtained also showed that the adsorption kinetics with the coefficient of determination ( R 2 ) for pseudo-second order (SSO) and pseudo-first order (SFO) were 0.99 and 0.96, respectively. Based on these results, the adsorption of fluoride onto GO is a pseudo-second-order kinetics type. According to the result, the Freundlich isotherm model showed a good fit to the experiment with R 2 (0.99). The adsorption capacity of the adsorbent was found to be 301.43 mg/g. Hence, this study showed that GO is the preferred adsorbent for the removal of fluoride from groundwater.